A broadband compact micro strip grid array antenna backed by an AMC reflector. Issue 11 (30th August 2022) - Hao, Gang; Xing, Shaohua; Liu, Yufeng; Zhang, Wenmei; Gao, Yang
Abstract: A broadband and compact micro strip grid array antenna (MGAA) is proposed. The proposed array is based on hourglass‐shaped loop elements, which are designed to reduce the size of the grid area in both horizontal and vertical directions with an area reduction of about 22%. To improve the radiation performance, a petaloid‐shaped artificial magnetic conductor (AMC) surface is adopted to replace the traditional metal ground. An air gap layer is introduced between the grid array layer and the AMC surface to enhance the gain and bandwidth of the antenna. A prototype antenna was fabricated and tested. The measured results show that the designed antenna has a wide impedance bandwidth ( S 11 < − 10 dB ), which is ranging from 4.63 to 6.08 GHz (25.0%). The 3‐dB gain bandwidth is from 5.23 to 6.45 GHz (21.0%) with a peak gain of 16.1 dBi at 5.8 GHz. The proposed MGAA consists of 14 radiating elements and possesses a compact size of 2.690 λ 0 × 2.690 λ 0 × 0.077 λ 0 ( λ 0 ‐the wavelength in free space at 5.8 GHz).